PENGARUH CAREER DEVELOPMENT, KOMPENSASI DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA DI PT RADIANT UTAMA INTERINSCO - Nindita Putri Safira Radityo (2022)
This research is a quantitative research that aims to determine the effects of Career Development, Compensation, and Work Discipline on Job Satisfaction. The sample in this study used 70 permanent employees at PT Radiant Utama Interinsco. The number of samples was calculated using the slovin formula with the sampling method using purposive sampling technique. Data collection was carried out through distributing questionnaires. Testing this research using the coefficient of determination test, T test, and F test with the help of the SmartPLS 4.0 program. The results of the tests carried out are (1) career development has a positive and significant effect on job satisfaction (2) compensation has a positive and significant effect on job satisfaction (3) work discipline has a positive and significant effect on job satisfaction (4) career development, compensation, and discipline work has a simultaneous effect on employee job satisfaction at PT Radiant Utama Interinsco.